The Geometry of Infinite-Dimensional Groups - Khesin, Boris; Wendt, Robert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This monograph gives an overview of various classes of infinite-dimensional Lie groups and their applications in Hamiltonian mechanics, fluid dynamics, integrable systems, gauge theory, and complex geometry. While infinite-dimensional groups often exhibit very peculiar features, this book describes unifying geometric ideas of the theory and gives numerous illustrations and examples, ranging from the classification of the Virasoro coadjoint orbits to knot theory, from optimal mass transport to moduli spaces of flat connections on surfaces. The text includes many exercises and open questions, and it is accessible to both students and researchers in Lie theory, geometry, and Hamiltonian systems.
Preface -- Introduction -- I Preliminaries -- II Infinite-dimensional Lie Groups: Their Geometry, Orbits and Dynamical Systems -- III Applications of Groups: Topological and Holomorphic Gauge Theories -- Appendices -- A1 Root Systems -- A2 Compact Lie Groups -- A3 Krichever-Novikov Algebras -- A4 Kähler Structures on the Virasoro and Loop Group Coadjoint Orbits -- A5 Metrics and Diameters of the Group of Hamiltonian Diffeomorphisms -- A6 Semi-Direct Extensions of the Diffeomorphism Group and Gas Dynamics -- A7 The Drinfeld-Sokolov Reduction -- A8 Surjectivity of the Exponential Map on Pseudo-Differential Symbols -- A9 Torus Actions on the Moduli Space of Flat Connections -- Bibliography -- Index.
Keywords: Mathematics; Algebraic geometry; Group theory; Topological groups; Lie groups; Global analysis (Mathematics).; Manifolds (Mathematics).; Geometry; Physics; Mathematics; Topological Groups, Lie Groups; Group Theory and Generalizations; Geometry; Mathematical Methods in Physics; Global Analysis and Analysis on Manifolds; Algebraic Geometry; Electronic books